Anti-infective effects of Brazilian Caatinga plants against pathogenic bacterial biofilm formation. (March 2015) - Silva, Laura Nunes; Trentin, Danielle da Silva; Zimmer, Karine Rigon; Treter, Janine; Brandelli, Clara Lia Costa; Frasson, Amanda Piccoli; Tasca, Tiana; Silva, Alexandre Gomes da; Silva, Márcia Vanusa da; Macedo, Alexandre José
Abstract Context: The local communities living in the Brazilian Caatinga biome have a significant body of traditional knowledge on a considerable number of medicinal plants used to heal several maladies. Objective: Based on ethnopharmacological data, this study screened 23 aqueous plant extracts against two well-known models of biofilm-forming bacteria: Staphylococcus epidermidis and Pseudomonas aeruginosa. Materials and methods: Crystal violet assay and scanning electron microscopy (SEM) were used to evaluate the effect of extracts on biofilm formation and measurements of the absorbance at 600 nm to assess bacterial growth. Selected extracts were investigated regarding the cytotoxicity by MTT assay using mammal cells and the qualitative phytochemical fingerprint by thin layer chromatography. Results: Harpochilus neesianus Mart. ex Nees. (Acanthaceae) leaves, Apuleia leiocarpa Vogel J. F. Macbr. (Fabaceae), and Poincianella microphylla Mart. ex G. Don L. P. Queiroz (Fabaceae) fruits showed non-biocidal antibiofilm action against S. epidermidis with activities of 69, 52, and 63%, respectively. SEM confirmed that biofilm structure was strongly prevented and that extracts promoted overproduction of the matrix and/or bacterial morphology modification. Poincianella microphylla demonstrated toxicity at 4.0 mg/mL and 2.0 mg/mL, A. leiocarpa presented toxicity only at 4.0 mg/mL, whereas H. neesianus presented the absence of toxicity against Vero cell line. Preliminary phytochemical analysis revealed the presence of flavonoids, terpenoids, steroids, amines, and polyphenols. Discussion and conclusions: This work provides a scientific basis which may justify the ethnopharmacological use of the plants herein studied, indicating extracts that possess limited mammal cytotoxicity in vitro and a high potential as a source of antibiofilm drugs prototypes.